Intake of F-100 and honey as an effort to improve the nutritional status of children with pediatric tuberculosis - Machfudz, Soeroyo; Rachmawaty, Farida Juliantina; Sabila, Aflifia Birruni (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Background: Stunting remains a significant nutritional challenge in Indonesia. If malnutrition in children is not addressed appropriately, it can lead to stunting. Children under five years old with pediatric tuberculosis (TB) are particularly susceptible malnutrition. Specific interventions are needed to prevent stunting in this vulnerable group.Objective: The study aimed to improve the nutritional status of children with pediatric TB to prevent stunting. Methods: This study included 44 children under five years old with pediatric TB, who were patients at a private hospital and clinic. The subjects were divided into four groups of 10-12 children based on their arrival for treatment. Group A received standard medicine, F-100, and pure honey; Group B received standard medicine and F-100; Group C received standard medicine and pure honey; and Group D received only standard medicine. The F-100 and pure honey were administered once daily. Each group was followed up for six weeks. Weight and height were measured before and after the intervention. Statistical analysis was performed with a 95% confidence level.Results: Administration of F-100 and/or honey significantly increased Z scores for height-for-age, weight-for-age, and weight-for-length/height between the pre-test and post-intervention (p < 0.05). Conversely, no significant improvement was observed in children receiving only standard medication (p > 0.05). The differences in Z score increases between groups, however, were not statisticallysignificant. Overall, the intervention reduced the prevalence of wasting (36.4% to 22.75%) and stunting (36.4% to 29.5%)Conclusion: Supplementation with F-100 and honey improved nutritional outcomes but did not show statistically significant differences between groups. Further research is recommended to explore the effects of increased frequency and duration of supplementation.